2018
DOI: 10.1007/s12975-018-0617-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Release of IL-6 After Stroke Contributes to Impaired Cerebral Autoregulation and Hippocampal Neuronal Necrosis Through NMDA Receptor Activation and Upregulation of ET-1 and JNK

Abstract: The sole FDA-approved drug treatment for ischemic stroke is tissue-type plasminogen activator (tPA). However, upregulation of JNK mitogen-activated protein kinase (MAPK) and endothelin 1 (ET-1) by tPA after stroke contributes to impaired cerebrovascular autoregulation. Wild-type (wt) tPA can bind to the lipoprotein-related receptor (LRP), which mediates vasodilation, or NMDA receptors (NMDA-Rs), exacerbating vasoconstriction. Elevations in IL-6, a marker of inflammation that accompanies stroke, are reported to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 31 publications
0
29
1
Order By: Relevance
“…26 Among various proin ammatory cytokines, IL-6 plays pivotal roles in local in ammation and cytotoxicity after ischemic brain injury, and is involved in the mechanism underlying the expansion of ischemic brain injury. 27,28 Blockade of IL-6 receptors has been shown to reduce infarct volume and improve cognitive function in an experimental model of ischemic stroke. 29 These earlier studies are concordant with the suppression of IL-6 by propofol observed in the current study after ischemic brain insult, as well as the reduction of infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…26 Among various proin ammatory cytokines, IL-6 plays pivotal roles in local in ammation and cytotoxicity after ischemic brain injury, and is involved in the mechanism underlying the expansion of ischemic brain injury. 27,28 Blockade of IL-6 receptors has been shown to reduce infarct volume and improve cognitive function in an experimental model of ischemic stroke. 29 These earlier studies are concordant with the suppression of IL-6 by propofol observed in the current study after ischemic brain insult, as well as the reduction of infarct volume.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TNF, IL-1α, and IL-6 released by lipopolysaccharide (LPS)-activated microglia are together sufficient to induce the A1 phenotype in astrocytes [46,47]. However, studies on A2 phenotype modulation in astrocytes are still rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…As such an approach would mimic intrinsic changes induced by brief and beneficial stimulations, it might be tolerated by brain and thus minimize potential side effects. This would also prolong the period before the brain becomes vulnerable to detrimental insult, enabling the brain to adapt or develop resistance (Stenzel-Poore et al, 2003), delay functional impacts like memory or motor deficits, and allow for efficient interventions (Armstead, Hekierski et al, 2018).…”
Section: Discussionmentioning
confidence: 99%